Scalable graphene fluoride sandwiched aramid nanofiber paper with superior high-temperature capacitive energy storage - Vu, Minh Canh; Kang, Hyoungku; Park, Pyeong Jun; Choi, Bong-Gil; Paik, Jong-Woo; Choi, Won-Kook; Islam, Md Akhtarul; Wang, Qing; Kim, Sung-Ryong (Elsevier BV, 2022)
High-performance capacitive energy storage under high voltages over a broad temperature range is eminently indispensable for the next generation of microelectronics and electrical power modules. The available dielectric polymer nanocomposites, unfortunately, are confined to the relatively low-temperature regimes (usually below 200 ?C) and that hinders their practical applications. This work presents the scalable fabrication of highly thermostable phosphorous crosslinked aramid nanofiber (PANF) paper with a sandwiched layer of high aspect-ratio electrically insulating graphene fluoride (GF) nanosheets prepared by ultrasonic spraying. The sandwiched layer remarkably diminishes the conduction current density and dielectric loss, thereby imparting the ANF paper exceptional breakdown strength and much-enhanced energy density at elevated temperatures. Owing to the excellent combination of ultrahigh breakdown strength and large displacement (~0.076 C.m(-2 )under 502 MV.m(-1)), the sandwich-structured AGA (PANF-GF-PANF) dielectric paper shows the maximal discharged energy density of 16.7 J.cm(-3) with a charge-discharge efficiency of 86% at 30 ?C and a record-high discharged energy density of 11.7 J.cm(-3 )with a charge-discharge efficiency of 87.2% under an applied electric field of 400 MV.(m-1) at 200 ?C. In addition, the flexible sandwich paper shows outstanding stability up to 500 ?C. This work opens up new possibilities for the mass production of flexible high-temperature dielectrics for capacitive energy devices operating in harsh environments.